ACTR-30. PHASE 1B/2 STUDY TO ASSESS THE CLINICAL EFFECTS OF PAMIPARIB (BGB-290) IN COMBINATION WITH RADIATION THERAPY (RT) AND/OR TEMOZOLOMIDE (TMZ) IN PATIENTS WITH NEWLY DIAGNOSED OR RECURRENT/REFRACTORY GLIOBLASTOMA (GBM). (5th November 2018) - Shih, Kent; Schiff, David; Kim, Lyndon; Battiste, James; Campian, Jian; Puduvalli, Vinay; Wen, Patrick; Cloughesy, Timothy; van den Bent, Martin; Pirzkall, Andrea; Wood, Katie; Wei, Rachel; et al.
Abstract: DNA damage caused by TMZ or RT sensitizes tumors to PARP inhibitors, especially in highly replicating tumors (eg, GBM). Pamiparib is a selective PARP1/2 inhibitor with potent PARP trapping that can cross the blood-brain barrier and has shown synergistic cytotoxicity with TMZ in nonclinical experiments. At 60mg BID, the human-equivalent dose-to-trough brain concentrations above the nonclinical efficacy threshold, pamiparib was generally well tolerated and showed antitumor activity in early clinical studies (NCT02361723; NCT03333915). This ongoing dose-escalation/expansion study (NCT03150862) will determine the safety/tolerability and antitumor effects of pamiparib (60mg BID)+RT and/or TMZ. The dose-escalation component consists of three arms. Arm A will establish tolerable duration of pamiparib (2, 4, 6 weeks)+RT in newly diagnosed GBM patients with unmethylated MGMT promoter (unmethyl-GBM). In Arm B, newly diagnosed patients with unmethyl-GBM will receive pamiparib+RT with increasing TMZ doses. Enrollment in Arm B will commence once RP2D for pamiparib+RT is established. In Arm C, patients with recurrent/refractory methylated- or unmethyl-GBM receive pamiparib with increasing TMZ doses. As of 28 March 2018, 15 patients were enrolled (A: 2-wk, n=3; 4-wk, n=6; C: TMZ [40mg], n=6). One DLT (grade 3 nausea) was reported in Arm C. Across arms, pamiparib-related AEs occurring in >3 patients were nausea (n=6) and fatigue (n=5). Two patients experienced three pamiparib-related AEs grade 3 (diarrhea [A: 4-wk, n=1]; fatigue and nausea [C: n=1]). All three resolved with concomitant medication and treatment interruption (A) or discontinuation (C). Of the seven patients with 1 tumor assessment, one (A: 4-wk) achieved an unconfirmed PR; four (A: 2-wk, n=2; 4-wk, n=2) had SD, and two (A: 2-wk, n=1; C: n=1) had PD. Preliminary data suggests pamiparib at 60mg BID is generally well tolerated by patients when administered 4 weeks concurrently with RT for newly diagnosed unmethyl-GBM and when combined with 40 mg TMZ for recurrent/refractory GBM.